An Analysis of Capital Market Using Network Approach - Reza Taghizadeh; Mohammad Abdzadeh Kanafi (تحقیقات مالی)
Objective Financial markets are considered to be a kind of complex network due to the interaction and interrelationship of its various actors. Therefore, the development of stock communication networks is an important issue for discovering potential connections between different companies. Therefore, the purpose of this research is to investigate and analyze the communication structure of companies in the capital market based on price, return, and trading volume of stock with a network approach.